Review of Campsicnemus (Diptera: Dolichopodidae) of the Marquesas, French Polynesia, with description of four new species groups - Evenhuis, Neal L. (Zootaxa, 2009)
The Marquesan species of Campsicnemus are reviewed and four new species groups: the gladiator group (Marquesan gladiator flies), the aa group (Marquesan vowel flies), the englundi group (Marquesan silly-walk flies), and the hihiroa group (Marquesan eyelash flies) are defined. Twelve new species are described and illustrated: Campsicnemus gladiator Evenhuis, n. sp. (gladiator group); C. aa Evenhuis, n. sp., C. ee Evenhuis, n. sp., C. ii Evenhuis, n. sp., C. oo Evenhuis, n. sp., C. uu Evenhuis, n. sp. (all in the aa group); C. englundi Evenhuis, n. sp.; C. cheesmanae Evenhuis, n. sp., C. plautus Evenhuis, n. sp.; (all in the englundi group); C. dytei Evenhuis, n. sp., C. hihiroa Evenhuis, n. sp., C. taratara Evenhuis, n. sp. (all in the hihiroa group). A key to all known French Polynesian species groups of Campsicnemus and to species within each species group in the Marquesas are given.